2021
DOI: 10.1590/1984-0462/2021/39/2020013
|View full text |Cite
|
Sign up to set email alerts
|

Patent Ductus Arteriosus Closure: Experience From a Tertiary Referral Center

Abstract: Objective: To characterize the number and methods of closure of Persistent Ductus Arteriosus (PDA) over a span of 16 years in a third level maternity hospital. Methods: Retrospective study of neonates born between January 2003 and Deccember 2018, who underwent ductus arteriosus closure by pharmacological, surgical and/or transcatheter methods. Gestational age, birth weight, number and methods of closures per year were evaluated. The success rate of the pharmacologic method was calculated, as well as the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In our study, 14% of children were born prematurely. The prematurity rate in our study was close to that in the Faim DR study (11%) [15]. However, other studies have shown a higher rate of premature births, such as Tort's study [13].…”
Section: Discussionsupporting
confidence: 84%
“…In our study, 14% of children were born prematurely. The prematurity rate in our study was close to that in the Faim DR study (11%) [15]. However, other studies have shown a higher rate of premature births, such as Tort's study [13].…”
Section: Discussionsupporting
confidence: 84%
“…8 Similarly, in a large retrospective study, pharmacological closure (with either indomethacin or ibuprofen) was the method of choice prior to surgical ligation. 32 This suggests that infants who received indomethacin may have experienced pharmacologic benefits for hsPDA, with a correspondingly lower rate of surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study, showed PDAs were less common in infants who were treated with indomethacin after the first day of life, compared to infants who were not treated with indomethacin (21% vs. 36.1%, p<0.001) 8 . Similarly, in a large retrospective study, pharmacological closure (with either indomethacin or ibuprofen) was the method of choice prior to surgical ligation 32 . This suggests that infants who received indomethacin may have experienced pharmacologic benefit for hsPDA, with a correspondingly lower rate of surgical intervention.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Treatment options include fluid restriction, pharmacological intervention with nonsteroidal antiinflammatory drugs (NSAIDs) or paracetamol, or closing the duct by surgical ligation or heart catheterization. [5] PDA closure, regardless of the type of method, also comes with risks. There is not always a consensus as to what gives the best prognosis for newborns, whether to wait or to close the PDA.…”
Section: Introductionmentioning
confidence: 99%
“…It was considered to be beneficial to use only one drug for both purposes. [5] Several studies have shown that acetaminophen has an efficacy similar to that of ibuprofen [8] but with a lower incidence of acute renal failure, oliguria, [9] platelet dysfunction, gastrointestinal bleeding, hyperbilirubinemia, [10] and necrotizing enterocolitis. [11] Therefore, the present study was conducted to evaluate the effect of oral acetaminophen in the closure of PDA in preterm neonates Noor Mohammad Noori 1 , Alireza Teimouri 1 , Abdollah Dehvari 1 , Somayeh Bagheie 1 , Hossein Ansari 1…”
Section: Introductionmentioning
confidence: 99%